ANALISIS NILAI PENDIDIKAN KARAKTER SATUA BALI I LACUR DALAM PEMBENTUKAN BUDI PEKERTI SISWA SD - Ida Bagus Yoga Swadnyana; Made Wahyu Jayanthi; Ni Putu Dian Pita Yanti; Ni Kadek Ginantri Setiari (STKIP Subang, 2026)
This study aims to analyze the character education values contained in the Balinese satua (traditional folktale) entitled